Endodontic Biofilm: Quo Vadis? - Ramírez Mora DDS, MSc, Tatiana (2016)
The main challenge in root canal treatment is to reduce bacterial load good enough to ensure success and to avoid reinfection. However, the evidence of biofilm along the root canal system and the inability of current instruments and irrigants to eliminate bacterial biofilm have built a barrier toward a higher favorable  prognosis of the root canal treatment, which has not change in the past five decades. Regarding this scenery, research in endodontics have been addressed to find new strategies or protocols to fight the war against biofilm. From conventional irrigants solutions to nanotechnology products are been tested, several in vitro and clinical studies are performance every day in this incessant search. So, what is next, where are we going in endodotics biofilm?